The Impact of Malignancy on Assisted Reproductive Outcomes for Cancer Survivors: A Retrospective Case–Control Study - Li, Yuehong; Cai, Xuefen; Dong, Binhua; Wang, Qi; Yang, Xiaohui; Yu, Aili; Wei, Huijuan; Ke, Zhanghong; Sun, Pengming; Zheng, Beihong; Sun, Yan (Frontiers in Oncology, 2022)
Background: Related studies have shown that it is safe for cancer patients to receive assisted reproduction. However, studies on whether a history of cancer affects long-term reproductive outcomes in women who underwent assisted reproductive technology (ART) are scarce. In this study, we evaluated the long-term reproductive outcomes of patients with malignant tumors receiving ART treatment and explored the impact of malignancy history on ART outcomes. Methods: A retrospective study, analyzed the clinical outcomes of patients with malignant tumors undergoing first in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles compared with age-matched healthy infertile women. We evaluated ovarian stimulation outcome, pregnancy rate, live birth rate, adverse obstetric outcome risk and birth outcome. Results: There were statistically significant differences in antral follicle count (AFC) (12.00±7.86 vs. 14.90±8.71, P=0.033), length of ovarian stimulation (9.98 ± 2.68 vs. 11.42±2.43, P=0.033) and endometrial thickness on the trigger day (10.16±3.11 vs. 10.84±2.17, P<0.001) between the two groups. The total gonadotropin dose, number of oocytes retrieved, fertilization rate, cleavage rate, high-quality embryo rate, blastocyst rate and first-time embryo-transfer (ET) implantation rate were nonsignificantly lower in the cancer group than in the control group (P>0.05). There were no significant differences in clinical pregnancy rate per ET cycle (32% vs. 40.39%, P=0.156), live birth rate per ET cycle (27% vs. 35.96%, P=0.119), miscarriage rate per ET cycle (5% vs. 4.43%, P=0.779), or preterm delivery rate per ET cycle (11.11% vs. 17.80%, P=0.547) between the two groups. Additionally, regression analysis showed that a history of malignancy was not a risk factor for reproductive outcomes. Conclusions: Overall, women with history of cancer conceives using ART is feasible and the long-term reproductive outcome is similar to these of healthy infertile. A history of cancer does not decrease the number of retrieved oocytes, does not increased the risk of obstetric outcomes as well as does not affect birth outcome. Larger studies are needed to further confirm this Conclusion.